Development of Cashier Application Using Delphi 7 & QR-Barcode at CV. Hidup Baru - Maulidi, Ilham; Iqbal, Taufiq; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The development of sales in today's era is very dependent on technology both in the sales process, marketing and cashier calculations. CV. Hidup Baru is engaged in the sale and marketing of grocery, cosmetic and baby equipment needs. The sales and data collection method uses a computer system. But in the price summation system in the company, errors often occur and there are not a few errors in printing customer invoices. New Life as well as the author himself. The method of data collection carried out in the process of preparing this report used two methods, namely the method of library research related to this material and field studies by conducting direct interviews with employees and direct observations with objects related to this research. The Prototyping method is used as a software development model and evaluation activities are also carried out as an assessment of the results of the prototype built. The results of the study indicate that the existence of an information system for the design of the Delphi7 program is expected to help CV. Hidup Baru and the results of evaluating the appearance of the current desktop application. With the prototype design, it is known that each category has increased usability values. Content, Organization and Readability previously had a value of 0.69 and increased to 0.72. The Navigation category was previously 0.72 to 0.77. The previous User Interface Design category was 0.63 to 0.74 and the previous Performance and Effectiveness category was 0.61 to 0.73.